Collective Traumas and the Development of Leader Values: A Currently Omitted, but Increasingly Urgent, Research Area - Tcholakian, Lara A.; Khapova, Svetlana N.; van de Loo, Erik; Lehman, Roger (Frontiers in Psychology, 2019)
The number of worldwide traumatic events is significant, yet the literature pays little attention to their implications for leader development. This article calls for a consideration of how collective trauma such as genocide and the Holocaust can shape the values of leaders, who are second- and third-generation descendants. Drawing on research on the transgenerational transmission of collective trauma and leader values, we show how collective trauma resides in (1) cultural rituals and artifacts, (2) community events and commemorations, and (3) family narratives is transmitted to leader descendants through at least three channels: social learning, social identity, and psychodynamics. We also offer propositions that recommend ways in which the transmission of these repositories can shape certain leader values that guide leader behaviors. Our conceptual review suggests that the transmission of collective trauma on leader development and leader values remains under-researched, offering prospects for new research and learning on the origins and seeds of leader development.